Pengaruh kualitas pelayanan terhadap kepuasan nasabah pada Islamic Bank Of Thailand Branch Bannangstar Province Yala - Adinan Yahring (SYNERGY: Jurnal Bisnis dan Manajemen, 2021)
The public's assessment of the bank is influenced by how the community perceives the bank's product or service received. Providing high quality service is a must to achieve customer satisfaction. For customers, quality of service and customer satisfaction comes from organized service. In simple terms, financial performance actually comes from customer loyalty. Loyal customers can save up to four to five times the cost of acquiring a new customer. This reality is a challenge in itself for the banking world, namely how to create customer desire to use the company's products and service providers and to build close relationships with the service community. The purpose of this study was to analyze the quality of service and community satisfaction of the Islamic Bank of Thailand Branch Bannangstar Province Yala and its effects. The method used is descriptive and quantitative methods; The technique of collecting data is interview, observation, questionnaire and documentation. This study concludes that based on the results of filling out the questionnaire by the research objects of this study regarding the quality of service, it is concluded that the service community feels very satisfying with the quality of service provided at the Islamic Bank of Thailand Branch, Bannangstar Province Yala. Based on the results of filling out the questionnaire by the research objects of this study, the satisfaction of the service community was also very satisfying because it had received good service at the Islamic Bank of Thailand Branch Bannangstar Province Yala. From the results of data processing, it is known that the quality of service has a significant effect on the variable customer satisfaction of the Islamic Bank of Thailand Branch Bannangstar Province Yala.